PERBANDINGAN KINERJA DAN KARAKTERISTIK KEUANGAN PERUSAHAAN PUBLIK DI PASAR MODAL INDONESIA DAN FILIPINA - Firdaus Indrajaya Tuharea (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2006)
Recovery process from crisis 1997 in all over ASEAN country had show a progress in 1999, where the economic condition is become batter than before. The report from World Economic Forum 2002 about economic growth in 80 countrys including ASEAN country have progress in their economic growth in 2001 and 2002 except Philippines and Indonesia. Report from World Investment report 2003 in their fact sheet, show that in all ASEAN countrys including Philippines have increase in transaction volume in their capital market, except Indonesia capital market. The fact that change in economic condition and recovery process from crisis doesn’t effect much to investor to invest their capital in philippines public company make some question, “is the public company in philippines have financial performance more batter than indonesia public company that also had decline in their economic condition?”. This research try ti find out the answer by compare financial performance (proxy by ratio) between public compani in philippines and indonesia. financial ratio use in this research is representation from liquidity ratio, solvency ratio, profitability ratio, and all that ratio compare by Independent Sample T-test in each observation time (2001 and 2002). The result from the test shows almost all ratio use (except ROA) indicate that financial performance in philippines public company is more batter then indonesia public company.